2000
DOI: 10.1042/cs20000002
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating cardiotrophin-1 in heart failure: relationship with parameters of left ventricular systolic dysfunction

Abstract: Cardiotrophin-1 (CT-1) is a cytokine that has been implicated as a factor involved in myocardial remodelling. The objective of the present study was to establish the relationship between circulating levels of CT-1 and measures of left ventricular size and systolic function in patients with heart failure. We recruited 15 normal subjects [six male; median age 60 years (range 30-79 years)] and 15 patients [11 male; median age 66 years (range 43-84 years)] with a clinical diagnosis of heart failure and echocardiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 21 publications
3
38
0
Order By: Relevance
“…In a multivariate model of the predictors of log wall motion index, the only signifi cant predictor was log CT-1. This demonstrates that CT-1 is elevated in heart failure in relation to the severity of LVSD 25,37 . Plasma CT-1 has high diagnostic effi cacy for heart failure (at concentration of 68 fmol/ml, sensitivity and specifi city were 95 % and 82.5 % respectively 64 ).…”
Section: Clinical Statuses and Ct-1mentioning
confidence: 91%
“…In a multivariate model of the predictors of log wall motion index, the only signifi cant predictor was log CT-1. This demonstrates that CT-1 is elevated in heart failure in relation to the severity of LVSD 25,37 . Plasma CT-1 has high diagnostic effi cacy for heart failure (at concentration of 68 fmol/ml, sensitivity and specifi city were 95 % and 82.5 % respectively 64 ).…”
Section: Clinical Statuses and Ct-1mentioning
confidence: 91%
“…Likewise, the level of circulating CT-1 was found to be a predictor of death or heart failure following acute myocardial infarction [73]. Most importantly, the studies in humans revealed a significant correlation between CT-1 expression, LV end-diastolic dimensions, and the severity of left ventricular systolic dysfunction [137]. CNTF could not be detected in the plasma of patients with moderate heart failure [91]; no additional data on systemic CNTF levels are available to date.…”
Section: General Overview On Gp130 Signalingmentioning
confidence: 94%
“…These include gp130 receptor internalization and degradation and induction of intrinsic suppressor of cytokine signaling (SOCS) proteins, such as SOCS-3. 4 We and others have shown that patients with congestive heart failure have raised plasma levels of CT-1 [5][6][7] that correspond to disease severity. 6 Enhanced CT-1 secretion seems to be an early event that occurs before onset of left ventricular systolic dysfunction and therefore may have an impact on disease progression.…”
Section: See P 1430mentioning
confidence: 99%
“…4 We and others have shown that patients with congestive heart failure have raised plasma levels of CT-1 [5][6][7] that correspond to disease severity. 6 Enhanced CT-1 secretion seems to be an early event that occurs before onset of left ventricular systolic dysfunction and therefore may have an impact on disease progression. 8 The observation that CT-1 concentrations were significantly higher in the coronary sinus than in the aorta 9 indicates that the heart is a prominent source of circulating CT-1 in humans.…”
Section: See P 1430mentioning
confidence: 99%